Comparison of Factors Related to Success in PIRLS: a Secondary Analysis of PIRLS42006 on Russian Sample - Yulia Tyumeneva (Voprosy obrazovaniya / Educational Studies Moscow, 2010)
The article presents the results of a further multidimensional analysis of PIRLS"2006 data on the Russian sample. In the first part, the author discusses research on the connection between various characteristics of the school and family and the child’s achievements in PIRLS. In particular, she demonstrates that children from different socio-demographic groups showed a non"uniform five year long dynamic of achievements. The conditions under which school resources begin to have an impact on students’ reading skills are determined. The author suggests optimal combinations of reading tasks and text comprehension tasks. The second part describes the procedure and results of a regression analysis of key variables relating to school and home learning environments. The conclusion is that school and family factors have an unequal impact on the reading skills of a child. A negative impact of certain factors on reading skills is shown. The author proceeds to discuss alternative interpretations of the results and the desirability of secondary analyses of international surveys.